Voluntary Exercise Induces Astrocytic Structural Plasticity in the Globus Pallidus - Tatsumi, Kouko; Okuda, Hiroaki; Morita-Takemura, Shoko; Tanaka, Tatsuhide; Isonishi, Ayami; Shinjo, Takeaki; Terada, Yuki; Wanaka, Akio (Frontiers in Cellular Neuroscience, 2016)
Changes in astrocyte morphology are primarily attributed to the fine processes where intimate connections with neurons form the tripartite synapse and participate in neurotransmission. Recent evidence has shown that neurotransmission induces dynamic synaptic remodeling, suggesting that astrocytic fine processes may adapt their morphologies to the activity in their environment. To illustrate such a neuron-glia relationship in morophological detail, we employed a double transgenic Olig2CreER/WT; ROSA26-GAP43-EGFP mice, in which Olig2-lineage cells can be visualized and traced with membrane-targeted GFP. Although Olig2-lineage cells in the adult brain usually become mature oligodendrocytes or oligodendrocyte precursor cells with NG2-proteoglycan expression, we found a population of Olig2-lineage astrocytes with bushy morphology in several brain regions. The globus pallidus (GP) preferentially contains Olig2-lineage astrocytes. Since the GP exerts pivotal motor functions in the indirect pathway of the basal ganglionic circuit, we subjected the double transgenic mice to voluntary wheel running to activate the GP and examined morphological changes of Olig2-lineage astrocytes at both the light and electron microscopic levels. The double transgenic mice were divided into three groups: Control group mice were kept in a cage with a locked running wheel for three weeks, Runner group were allowed free access to a running wheel for three weeks, and the Runner-Rest group took a sedentary three-week rest after a three-week running period. GFP immunofluorescence analysis and immunoelectron microscopy revealed that astrocytic fine processes elaborated complex arborization in the Runner mice, and reverted to simple morphology comparable to that of the Control group in the Runner-Rest group. Our results indicated that the fine processes of the Olig2-lineage astrocytes underwent plastic changes that correlated with overall running activities, suggesting that they actively participate in motor functions.